Preparation and characterization of composite polymeric membranes for gas separation - Ng, Karen Pei Wen. (2011)
In this project, five different concentrations 5 wt%, 10wt%, 15 wt% , 20wt% and 25wt% of fumed nano-silica were added into PVDF matrix and four pyrolysis temperatures 300 ˚C, 350 ˚C, 400 ˚C and 500 ˚C were used to prepare polymeric composite membranes. The effects of fumed silica concentrations and pyrolysis temperatures on the morphology and gas transport properties of the resulted mixed matrix polymeric membranes were investigated. The morphology of the resulted membranes was studied based on scanning electron microscopy images. Energy dispersive X-ray was used to find out the elemental composition of the composite membranes while gas permeation tests were conducted to assess their gas transport properties. 20 wt% of fumed silica was found to be the optimum concentration that allowed the membrane to have the best gas permeability and selectivity among the five different silica concentrations. It was also found out that the membrane containing 20 wt% of fumed silica that was pyrolysed at 400 ˚C had the highest selectivity among the four different pyrolysis temperatures while maintaining satisfactory permeability.